Soil carbon dominates total carbon stocks in robusta coffee agroforests in tropical Malinau, Kalimantan: evidence from field data and UAV-satellite mapping - Adi Sutrisno; Etty Wahyuni; Mohammad Wahyu Agang; Tjahjo Tri Hartono; Mas Davino Sayaza; Dwi Santoso; Deny Titing; Erwan Kusnadi; Elida Novita; Rahmat Pramulya; Devi Maulida Rahmah (Agroforestry Systems, 2026)

An adaptive multi-stage hybrid ensemble with iterative feature optimization for oil palm seed system analytics - Rahmad B.Y Syah; Retna Astuti Kuswardani; Marischa Elveny; Hartono (Computers and Electronics in Agriculture, 2026)

Capitalizing on Geopark Master Plan in Pursuing Sustainable Development Goals: Case Study of the Kebumen Aspiring UNESCO Global Geopark, Kebumen Regency, Indonesia - Bambang Yunianto; Chusni Ansori; Hanang Samodra; Sam Permanadewi; Hartono; Triswan Suseno; Ijang Suherman; Sri Sugiarti; Desi Cahyaningtyas (Geoheritage, 2026)

Consolidation of soft soils using prefabricated vertical drains: a systematic review of modeling advances, hybrid preloading innovations, and field performance - Willis Diana; Edi Hartono (Innovative Infrastructure Solutions, 2026)

Enhancing village-level spatial planning with unmanned aerial vehicles: A comparative study of direct georeferencing and ground control points - Gunawan Setyo Prabowo; Suprapedi Suprapedi; Muhammad Bisri; Wayan Firdaus Mahmudy; Ari Sugeng Budiyanta; Nur Sugi; Try Kusuma Wardana; Aries Asrianto Ramadian; Hartono Hartono; Rudi Choirul Anwar; Unggul Satrio Yudhotomo (Applied Geomatics, 2026)

Exploring the Interplay Between Water Source Choices and Perceptions of Hydrological Disaster Risks: Insights from Semarang’s Coastal Communities - Arya Rezagama; Djoko Mulyo Hartono; Tri Edhi Budhi Soesilo; Hayati Sari Hasibuan (International Journal of Environmental Research, 2026)

Constraining self-sourcing stratigraphic plays in North Sumatra: Integration of basin-petroleum system and stratigraphic forward modeling - Qi Adlan; Barry M. Hartono; Harya D. Nugraha; Adhipa Herlambang; Waleed AlGharbi; Eriko Sabra (Marine and Petroleum Geology, 2025)

Impact of enzymatic browning on in vitro protein digestibility of isoelectric precipitated RuBisCO from alfalfa: Validation by high resolution ion mobility mass spectrometry - Hartono Tanambell; Emilie Aagaard; Casper Rasmussen; Marianne Danielsen; Louise Juul; Trine Kastrup Dalsgaard (Food Chemistry, 2025)

Proof-of-concept: Ultrafiltration as a pre-treatment for the anion exchange chromatography of RuBisCO from alfalfa - Hartono Tanambell; Marianne Danielsen; Anders Hauer Møller; Trine Kastrup Dalsgaard (Food and Bioproducts Processing, 2025)

Unpacking the determinants of emission intensity changes in Indonesia: A multiplicative structural decomposition approach - Djoni Hartono; Sasmita Hastri Hastuti; Robi Kurniawan; Usep Surahman; Yulesta Putra; Hiroaki Shirakawa (Energy and Climate Change, 2025)

Understanding aerosol growth and emissions: CO2 capture in the RWE Niederaussem pilot plant using CESAR1 - Hallvard F. Svendsen; Hanna K. Knuutila; Ardi Hartono; Diego Morlando; Maxime Francois; Peter Moser; Georg Wiechers (International Journal of Greenhouse Gas Control, 2025)

Igneous intrusion effect on the geochemistry of Late Miocene Onnagawa mudstone: implication on the atypical hydrocarbon generation of Akita Basin, Japan - Barry Majeed Hartono; Shun Chiyonobu; Takuto Ando (Applied Geochemistry, 2025)

Utilization potential of low-cost media: Recombinant exoglucanase production in Pichia pastoris - Urip Perwitasari; Faisal Diniamal Hartono; Asrul Muhamad Fuad; Anis Herliyati Mahsunah; Hendi Saleh Permana; Dadang Suhendar; Edi Wahjono; Eka Triwahyuni; Sri Sugiwati; Irika Devi Anggraini; Septhian Marno; Trisanti Anindyawati (Biocatalysis and Agricultural Biotechnology, 2025)

MicroNIR spectroscopy with chemometric analysis provides rapid protein content evaluation and prediction of semi-refined flaxseed protein extract produced via pulsed electric field (PEF)-assisted extraction - Jervee M. Punzalan; Peter Hartono; Sara J. Fraser-Miller; Sze Ying Leong; Kevin Sutton; Gert-Jan Moggre; Keith C. Gordon; Indrawati Oey (Food Chemistry, 2025)

Determining factors and strategy in sustainable fecal sludge management services - Nadia Paramita; Rachmadhi Purwana; Djoko Mulyo Hartono; Tri Edhi Budhi Soesilo (Groundwater for Sustainable Development, 2025)

Corrigendum to “Partitioning of proteins and small molecular weight compounds from alfalfa juice during ultrafiltration” [Food Bioscience, (62), December 2024, 105044] - Hartono Tanambell; Marianne Danielsen; Sofie Freund; Signe Hjerrild Nissen; Anders Hauer Møller; Milena Corredig; Trine Kastrup Dalsgaard (Food Bioscience, 2025)

mRNA expression of kidney aquaporins and blood composition of meat-type chickens raised with or without glucose supplementation under cyclic heat or thermoneutral condition - Oluwatomide W. Ariyo; Josephine Kwakye; Selorm Sovi; Bikash Aryal; Evan Hartono; Ahmed F.A. Ghareeb; Marie C. Milfort; Alberta L. Fuller; Romdhane Rekaya; Samuel E. Aggrey (Journal of Thermal Biology, 2024)

Partitioning of proteins and small molecular weight compounds from alfalfa juice during ultrafiltration - Hartono Tanambell; Marianne Danielsen; Sofie Freund; Signe Hjerrild Nissen; Anders Hauer Møller; Milena Corredig; Trine Kastrup Dalsgaard (Food Bioscience, 2024)

Past and future land use change dynamics: assessing the impact of urban development on agricultural land in the Pantura Jabar region, Indonesia - Laju Gandharum; Djoko Mulyo Hartono; Asep Karsidi; Mubariq Ahmad; Yosef Prihanto; Sidik Mulyono; Heri Sadmono; Hartanto Sanjaya; Lena Sumargana; Fauziah Alhasanah (Environmental Monitoring and Assessment, 2024)

Disentangling divergent factors controlling bacterial and fungal communities in topsoil and subsoil horizons across environmental gradients of tropical volcanic regions - Han Lyu; Kozue Sawada; Ruohan Zhong; Method Kilasara; Arief Hartono; Randy A. Dahlgren; Shinya Funakawa; Tetsuhiro Watanabe (CATENA, 2024)

In vitro protein digestibility of RuBisCO from alfalfa obtained from different processing histories: Insights from free N-terminal and mass spectrometry study - Hartono Tanambell; Marianne Danielsen; Tove Gulbrandsen Devold; Anders Hauer Møller; Trine Kastrup Dalsgaard (Food Chemistry, 2024)

A stochastic differential equation model for predator-avoidance fish schooling - Aditya Dewanto Hartono; Linh Thi Hoai Nguyen; Tôn Việt Tạ (Mathematical Biosciences, 2024)

Analyzing public discourse on photovoltaic (PV) adoption in Indonesia: A topic-based sentiment analysis of news articles and social media - Yun Prihantina Mulyani; Anas Saifurrahman; Hilya Mudrika Arini; Arwindra Rizqiawan; Budi Hartono; Dhanan Sarwo Utomo; Agnessa Spanellis; Macarena Beltran; Kevin Marojahan Banjar Nahor; Dhyana Paramita; Wira Dranata Harefa (Journal of Cleaner Production, 2024)

The Impacts of Households on Carbon Dioxide Emissions in Indonesia - Djoni Hartono; Akbar Nikmatullah Dachlan; Sasmita Hastri Hastuti; Fitri Kartiasih; Novani Karina Saputri; Robi Kurniawan; Usep Surahman; Fadjar Goembira; Hiroaki Shirakawa (Environmental Processes, 2023)

Investigating drivers of active nitrification in organic horizons of tropical forest soils - Shinichi Watanabe; Makoto Shibata; Yoshiko Kosugi; Lion Marryanna; Keitaro Fukushima; Arief Hartono; Shinya Funakawa (Soil Ecology Letters, 2023)

Geochemistry of carbonate-derived oils in the Seram Basin, eastern Indonesia: A new hydrocarbon generation, migration, and preservation model for exploration in fold-thrust belts - Barry Majeed Hartono; Eddy Ariyono Subroto; Asep Heri Patria Kesumajana; Roy Andrianto; Galung Malvinas; Joko Wahyudiono (Journal of Asian Earth Sciences, 2023)

Supramolecular structure modification of RuBisCO from alfalfa during removal of chloroplastic materials - Hartono Tanambell; Anders Hauer Møller; Laura Roman; Milena Corredig; Trine Kastrup Dalsgaard (Innovative Food Science & Emerging Technologies, 2023)

The convergence of energy intensity in developing countries: a spatial econometric analysis with Indonesia’s provincial panel data - Rhisa Azaliah; Hengky Kurniawan; Djoni Hartono; Putu Angga Widyastaman (Environment, Development and Sustainability, 2023)

Phylogenetic and diversity analyses revealed that leek yellow stripe virus population consists of three types: S, L, and N - Adyatma Irawan Santosa; Filiz Randa-Zelyüt; Ali Karanfil; Savaş Korkmaz; Sedyo Hartono; Filiz Ertunç (Virus Genes, 2023)

The impact of FDI on energy intensity: a spatial econometric analysis of Indonesian provinces - Atina Saraswati; Djoni Hartono; Witri Indriyani (Journal of Environmental Studies and Sciences, 2022)

The effect of environmental awareness on motivation in adopting farming conservation techniques in the various agro-ecological zones: a case study in critical land of Java Island, Indonesia - Maria; Irham; Slamet Hartono; Lestari Rahayu Waluyati (Environment, Development and Sustainability, 2022)

Tangerine tomatoes: origin, biochemistry, potential health benefits and future prospects - Hartono Tanambell; Karen Suzanne Bishop; Siew Young Quek (Critical Reviews in Food Science and Nutrition, 2021)

Remote sensing versus the area sampling frame method in paddy rice acreage estimation in Indramayu regency, West Java province, Indonesia - Laju Gandharum; Mari E. Mulyani; Djoko M. Hartono; Asep Karsidi; Mubariq Ahmad (International Journal of Remote Sensing, 2021)

The drivers of energy-related CO2 emission changes in Indonesia: structural decomposition analysis - Sasmita Hastri Hastuti; Djoni Hartono; Titi Muswati Putranti; Muhammad Handry Imansyah (Environmental Science and Pollution Research, 2021)

Taming the flagellar motor of pseudomonads with a nucleotide messenger - Guang‐Lei Ma; Hartono Chandra; Zhao‐Xun Liang (Environmental Microbiology, 2020)
Summary Pseudomonads rely on the flagellar motor to rotate a polar flagellum for swimming and swarming, and to sense surfaces for initiating the motile‐to‐sessile transition to adopt a surface‐dwelling lifestyle. Deciphering the function and regulation of the flagellar motor is of paramount importance for understanding the behaviours of environmental and pathogenic pseudomonads. Recent studies disclosed the preeminent role played by the messenger c‐di‐GMP in controlling the real‐time performance of the flagellar motor in pseudomonads. The studies revealed that c‐di‐GMP controls the dynamic exchange of flagellar stator units to regulate motor torque/speed and modulates the frequency of flagellar motor switching via the chemosensory signalling pathways. Apart from being a rotary motor, the flagellar motor is emerging as a mechanosensor that transduces surface‐induced mechanical signals into an increase of cellular c‐di‐GMP concentration to initiate the cellular programs required for long‐term colonization. Collectively, the studies generate long‐awaited mechanistic insights into how c‐di‐GMP regulates bacterial motility and the motile‐to‐sessile transition. The new findings also raise the fundamental questions of how cellular c‐di‐GMP concentrations are dynamically coupled to flagellar output and the proton‐motive force, and how c‐di‐GMP signalling is coordinated spatiotemporally to fine‐tune flagellar response and the behaviour of pseudomonads in solutions and on surfaces.

Combined effects of nitrification inhibitor and zeolite on greenhouse gas fluxes and corn growth - Oslan Jumadi; Yusminah Hala; R. Neni Iriany; Andi Takdir Makkulawu; Junja Baba; Hartono; St. Fatmah Hiola; Kazuyuki Inubushi (Environmental Science and Pollution Research, 2020)

Emissions of nitrous oxide and methane from rice field after granulated urea application with nitrification inhibitors and zeolite under different water managements - Oslan Jumadi; Hartono Hartono; Andi Masniawati; R. Neny Iriany; Andi Takdir Makkulawu; Kazuyuki Inubushi (Paddy and Water Environment, 2019)

Assessment of causes and future deforestation in the mountainous tropical forest of Timor Island, Indonesia - Eko Pujiono; Ronggo Sadono; Hartono; Muhammad Ali Imron (Journal of Mountain Science, 2019)

The p27 open reading frame of tomato infectious chlorosis virus encodes a suppressor of RNA silencing - Takaaki Mashiko; Wei-Qin Wang; Sedyo Hartono; Gede Suastica; Yutaro Neriya; Hisashi Nishigawa; Tomohide Natsuaki (Journal of General Plant Pathology, 2019)

New recombinant of Tomato leaf curl New Delhi virus infecting melon in Indonesia - Fariha Wilisiani; Takaaki Mashiko; Wei-Qin Wang; Tomohiro Suzuki; Sedyo Hartono; Yutaro Neriya; Hisashi Nishigawa; Tomohide Natsuaki (Journal of General Plant Pathology, 2019)

Smoke detections and visibility estimation using Himawari_8 satellite data over Sumatera and Borneo Island Indonesia - Heri Ismanto; Hartono Hartono; Muh Aris Marfai (Spatial Information Research, 2019)

First report of the complete genomic sequences from Indonesian isolates of bamboo mosaic virus and detection of genomic recombination events - Satomi Abe; Yutaro Neriya; Kengo Noguchi; Sedyo Hartono; Sri Sulandari; Susamto Somowiyarjo; Asad Ali; Hisashi Nishigawa; Tomohide Natsuaki (Journal of General Plant Pathology, 2019)

Indonesian rainfall variability during Western North Pacific and Australian monsoon phase related to convectively coupled equatorial waves - Ida Pramuwardani; Hartono; Sunarto; Ardhasena Sopaheluwakan (Arabian Journal of Geosciences, 2018)

Probing the toxicity mechanism of multiwalled carbon nanotubes on bacteria - Maria R. Hartono; Ariel Kushmaro; Xiaodong Chen; Robert S. Marks (Environmental Science and Pollution Research, 2018)

Mangrove biomass carbon stock mapping of the Karimunjawa Islands using multispectral remote sensing - Pramaditya Wicaksono; Projo Danoedoro; Hartono; Udo Nehren (International Journal of Remote Sensing, 2016)

Use of Bamboo Powder Waste for Removal of Bisphenol A in Aqueous Solution - Maria R. Hartono; Ali Assaf; Gerald Thouand; Ariel Kushmaro; Xiaodong Chen; Robert S. Marks (Water, Air, & Soil Pollution, 2015)

Yellowing disease of tomato caused by Tomato chlorosis virus newly recognized in Japan - Tomoki Hirota; Tomohide Natsuaki; Tamotsu Murai; Hisashi Nishigawa; Kenji Niibori; Kakushi Goto; Sedyo Hartono; Gede Suastika; Seiichi Okuda (Journal of General Plant Pathology, 2010)

Yellowing disease of tomatoes caused by Tomato infectious chlorosis virus newly recognized in Japan - Sedyo Hartono; Tomohide Natsuaki; Haruki Sayama; Hiroki Atarashi; Seiichi Okuda (Journal of General Plant Pathology, 2003)

BC3H1 MYOGENIC CELLS PRODUCE AN INFECTIOUS ECOTROPIC MURINE LEUKEMIA VIRUS - SANDRA B. SHARP; MARIA VILLALVAZO; ALEX ESPINOSA; SAGAR DAMLE; XIOMARA PADILLA; JOHN HARTONO; RODOLFO GONZALEZ; SON VU (In Vitro Cellular & Developmental Biology - Animal, 2002)